2017
DOI: 10.1017/s0007114517002689
|View full text |Cite
|
Sign up to set email alerts
|

Effects of partial replacement of maize in the diet with crude glycerin and/or soyabean oil on ruminal fermentation and microbial population in Nellore steers

Abstract: The objective of this study was to determine whether a combination of crude glycerin (CG) and soyabean oil (SO) could be used to partially replace maize in the diet of Nellore steers while maintaining optimum feed utilisation. Eight castrated Nellore steers fitted with ruminal and duodenal cannulas were used in a double 4×4 Latin square design balanced for residual effects, in a factorial arrangement (A×B), when factor A corresponded to the provision of SO, and factor B to the provision of CG. Steers feed SO a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 61 publications
0
9
0
1
Order By: Relevance
“…This result is in agree with studies of Hristov et al (2004) who reported that protozoa are sensitive to C18:3, C18:2, and C18:1. In Nellore steers also was observed a directly inhibition of ruminal protozoa and Archaea by diets containing soybean oil sources (GRANJA-SALCEDO et al, 2017c). Was observed an interaction between SH × SG supplements on ruminal Archaea abundance.…”
Section: Discussionmentioning
confidence: 79%
“…This result is in agree with studies of Hristov et al (2004) who reported that protozoa are sensitive to C18:3, C18:2, and C18:1. In Nellore steers also was observed a directly inhibition of ruminal protozoa and Archaea by diets containing soybean oil sources (GRANJA-SALCEDO et al, 2017c). Was observed an interaction between SH × SG supplements on ruminal Archaea abundance.…”
Section: Discussionmentioning
confidence: 79%
“…In the rumen, the significantly increased microbes of yak calves in the maternal grazing group were mostly involved in the utilization of fibrous carbohydrates, including Treponema, and Fibrobacter (Kudo et al, 1987;Mansfield et al, 1994;Klevenhusen et al, 2017). In contrast, the significantly increased microbes of yak calves in the barn feeding groups were mostly involved in the utilization of non-fibrous carbohydrate, including the Sharpea, Sphingomonas, Atopobium, Syntrophococcus, Clostridium_XIVb, Acinetobacter, Oscillibacter, Dialister, Desulfovibrio, Bacteroides, Lachnospiracea_incertae_sedis, and Clostridium_sensu_stricto, which have also been proven to be related to increased rumen fermentation in the barn feeding group, especially the increased production of propionate (Lu et al, 2005;Edwards et al, 2017;Granja-Salcedo et al, 2017;Zhang et al, 2017). These results again proved that the different nutrient compositions could lead to different abundances and functions of microorganisms, which could further influence the utilization of nutrients.…”
Section: Discussionmentioning
confidence: 95%
“…For instance, the Pseudobutyrivibrio, Clostridium IV, and Desulfovibrio could generate butyrate by utilizing the starch (Kopecný et al, 2003;Balamurugan et al, 2008;Wang et al, 2013), and the Selenomonas, Brachybacterium, and Haemophilus could mainly take part in the propionate production process by utilizing the non-fibrous carbohydrates (Michel and Macy, 1990;Müller et al, 2010). Moreover, the abundance of Coprococcus, Sphingomonas, and Dialister has been widely suggested to be positively correlated with the increased starch supplementation, which suggested that these three genera could take part in the utilization of starch (Khafipour et al, 2009;Granja-Salcedo et al, 2017;Zhang et al, 2017). Meanwhile, the cellulose-decomposing and hemicellulosedecomposing related bacteria were also significantly increased in the yak calves from the SA group compared with those observed in the non-alfalfa supplemented groups (the CON or S group).…”
Section: Altered Gastrointestinal Microbiota In Response To Alfalfa Amentioning
confidence: 99%